Physiochemical properties of Jatropha curcas seed oil from different origins and candidate plus plants (CPPs) - A K M, Aminul Islam; Yaakob, Zahira; Anuar, Nurina; Primandari, Sri Rizki Purti; Osman, Mohamad (Springer Berlin, 2011)
The physicochemical properties of Jatropha seed oil from 9 geographical origins and 24 candidate plus plants (CPPs) were evaluated. The yield of seed oil obtained by Soxhlet extraction using n-hexane as solvent varied from 40.0% (Malaysia) to 48.4% (Vietnam) among seeds from different origins and 32.1% (CPP-17) to 48.8% (CPP-01) (w/w) among CPPs. Density, specific gravity, and refractive index of oil showed very little differences among all the seed sources. Oil from Borneo had the highest free fatty acid (FFA) content (2.3%) and a South African sample had the lowest FFA (0.4%), as oleic acids. Seed oil of CPP-13 had the highest FFA content (1.2%) and seed oil of CPP-17 the lowest (0.3%). Most of the CPPs in this study had an FFA content of less than 1%. Jatropha seed oil of Philippine origin had the highest iodine value (187.3 mg/g oil) and seed oil from Borneo the lowest (83.5 mg/g oil). The lowest saponification values were obtained from seed oil of Philippine origin (189.5 mg KOH/g) and CPP-22 (183.3 mg KOH/g oil) from Malaysia. The maximum higher heating value (40.3 MJ/kg) was obtained from seed oil from Borneo. The cetane numbers range from 25.4 (Indonesia) to 56.0 (Borneo) among the oils of base material and 46.4 (CPP-15) to 53.7 (CPP-06) among CPPs. This study gives basic information of relevance for biodiesel production using Jatropha seeds from various origins.